Edukasi Fisioterapi Mengenai Pencegahan Nyeri Leher pada Komunitas Pekerja Pabrik Keripik Tempe Sanan - Nadhila Khairunisa; Zidni Imanurrohmah Lubis; Rizal Septian (Lembaga Pengembangan Kinerja Dosen, 2025)
Physiotherapy is a form of health service aimed at individuals and communities. The scope of physiotherapy services is to develop, maintain, and restore movement and body function throughout the life span. This service can be done through a promotive, preventive, curative, and rehabilitation approach. One of the many cases of physiotherapy is musculoskeletal complaints. Musculoskeletal complaints can occur due to habits carried out during work. If the body position is not correct and maintained for a long duration, it can trigger the emergence of musculoskeletal complaints. Work that lasts for a long time will decrease a person's body ability and can cause complaints and disorders in the body, especially musculo problems, one of which is neck pain. Neck pain is a multifactorial disease and is a major problem in society today. Some risk factors for neck pain, such as old age, female gender, low social support, and non-ergonomic work postures. The method of community physiotherapy activities used is to provide health promotion counseling and education regarding physiotherapy management in the form of stretching that can be done independently. The media used are leaflets and posters. The purpose of this counseling is to provide education and physiotherapy treatment related to neck pain in Keripik Tempe Sanan workers so that they can improve the complaints that have been felt and minimize the occurrence of injuries.